2020
DOI: 10.1038/s41598-020-67255-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxygen Delivery, Metabolism, and Extraction Fraction during Long-Term Bilateral Common Carotid Artery Occlusion in Rats

Abstract: Retinal functional, biochemical, and anatomical changes have been previously reported in long-term experimental permanent bilateral common carotid artery occlusion (BccAo). the purpose of the current study was to investigate progressive reductions in retinal oxygen metabolism (Mo 2) due to inadequate compensation by oxygen delivery (Do 2) and extraction fraction (oef) after BccAo. twentynine rats were subjected to BCCAO and were imaged after 3 hours, 3 days, 7 days, or 14 days. Six rats underwent a sham proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, well-developed collateral circulation has chances to prevent this phenomenon in humans [6,34]. Experimentally, to induce ocular ischemia, bilateral occlusions of CCAs were applied to adult rats due to their well-developed collateral circulation [8][9][10]. Adult black mice (C57BL/6) could not be subjected to bilateral occlusions of CCAs in that they die during/after the surgery [11,20], of which outcome is related to a lack of the complete Circle of Willis in adult black mice (especially, the missing of the posterior communicating artery) [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, well-developed collateral circulation has chances to prevent this phenomenon in humans [6,34]. Experimentally, to induce ocular ischemia, bilateral occlusions of CCAs were applied to adult rats due to their well-developed collateral circulation [8][9][10]. Adult black mice (C57BL/6) could not be subjected to bilateral occlusions of CCAs in that they die during/after the surgery [11,20], of which outcome is related to a lack of the complete Circle of Willis in adult black mice (especially, the missing of the posterior communicating artery) [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are limited experimental animal models for retinal degeneration in OIS. Using bilateral occlusions of CCAs, rats have been widely used for understanding the pathological mechanism for retinal degeneration in OIS [8][9][10]. Relatively, mice have not been commonly utilized, as there exist the limitations for the model development using bilateral occlusions of CCAs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These timepoints were chosen based on our previous studies that demonstrated impairments in oxygen metrics after these durations of BCCAO. 46 48 After each duration of BCCAO, a randomly selected eye in each rat was imaged during two fractions of the inspired oxygen (FiO 2 ) condition: first under 21% O 2 inspiration (spontaneous room air breathing [RA]) and then immediately after 15 minutes of 100% O 2 inspiration (hyperoxia). Eight of the rats in the 30-minute BCCAO group were also imaged prior to BCCAO (baseline).…”
Section: Methodsmentioning
confidence: 99%
“…The common carotid arteries were accessed via a midline prelaryngeal incision, dissected from the sympathetic and vagus nerves and ligated, as previously described. 47 , 48 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation